Harlequins Histrionicus histrionicus in a Rocky Mountain watershed I: Background and general breeding ecology - Hunt, Bill; Ydenberg, Ron (Wildfowl, 2000)
The Maligne Valley, a watershed draining into the Athabasca River in the Rocky Mountains, in Jasper National Park, Canada, is a breeding area for Harlequin Ducks (Histrionicus histrionicus). Based on peak counts, some 30 - 40 adults enter the valley each spring, arriving in early May along the Athabasca River. Numbers build steadily in the valley until the period of peak flow, and individuals are highly faithful to particular sections of the main watercourse. Feeding is intensive prior to nest initiation. Harlequins use lakes, outlets, rivers, and tributaries in the valley in a variety of ways. Along the Lower Maligne River, a few Harlequin pairs defend territories, but the majority of birds feed in aggregations at major lake outlets and inlets, likely highly productive places. On Maligne Lake birds feed in scattered pairs, generally situated at stream inlets. Females begin nesting in mid-June following peak flow, and males depart the valley shortly thereafter. Nests are placed along both the main course of the Maligne River and along several tributaries, but the upper and lower sections of the Maligne River accounted for 11 of the 14 broods located. Many females move their broods to two large lakes for rearing.